2022
DOI: 10.1186/s13052-022-01327-1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of anthropometric indices and their relationship with maternal nutritional literacy and selected socio-economic and demographic variables among children under 5 years old

Abstract: Background Considering the destructive effects of malnutrition on the growth, development, and health of children and the importance of identifying the factors affecting it, the present study aimed to investigate the status of anthropometric indices and their relationship with maternal nutritional literacy and selected socio-economic and demographic variables among children under 5 years old. Methods This cross-sectional study was conducted on 405 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
0
8

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 18 publications
1
2
0
8
Order By: Relevance
“…Disamping itu, faktor mendasar seperti tingkat pendidikan, pengetahuan dan ekonomi berperan dalam masalah gizi pada balita. [4][5][6][7][8] Khususnya terkait dengan perekonomian penduduk dunia setelah dihadapkan dengan permasalahan pandemi COVID-19 selama dua tahun lalu sampai saat ini masih ditemukan kasusnya, turut mempengaruhi kejadian gizi kurang pada balita termasuk di Indonesia. Permasalahan ini dikaitkan dengan kemampuan penduduk dalam menyiapkan makanan yang sehat dan bergizi, kunjungan ke fasilitas kesehatan, air bersih, dan sanitasi.…”
Section: Pendahuluanunclassified
See 2 more Smart Citations
“…Disamping itu, faktor mendasar seperti tingkat pendidikan, pengetahuan dan ekonomi berperan dalam masalah gizi pada balita. [4][5][6][7][8] Khususnya terkait dengan perekonomian penduduk dunia setelah dihadapkan dengan permasalahan pandemi COVID-19 selama dua tahun lalu sampai saat ini masih ditemukan kasusnya, turut mempengaruhi kejadian gizi kurang pada balita termasuk di Indonesia. Permasalahan ini dikaitkan dengan kemampuan penduduk dalam menyiapkan makanan yang sehat dan bergizi, kunjungan ke fasilitas kesehatan, air bersih, dan sanitasi.…”
Section: Pendahuluanunclassified
“…9,10 Hasil penelitian sebelumnya menemukan hasil yang tidak konsisten terkait dengan faktor penyebab terjadinya permasalahan gizi kurang pada anak. [4][5][6][7][8] Berdasarkan hal tersebut dan penjelasan sebelumnya maka penelitian ini bertujuan untuk mengidentifikasi faktor yang paling berkontribusi terhadap gizi kurang pada balita yang berusia 2-5 tahun di Kota Padang.…”
Section: Pendahuluanunclassified
See 1 more Smart Citation
“… 22 Compared to knowledge, nutrition literacy is a more comprehensive concept that consists of not only the acquisition of nutritional knowledge but also the application of knowledge, which assesses whether an individual is able to help themselves solve nutrition problems independently. Studies on nutrition literacy of patients primarily focus on healthy adults, 23 children’s parents 24 or pregnant women. 25 Research 26 related to breast cancer patients demonstrated that their nutritional knowledge was inadequate, with only 30% improving their diet after treatment.…”
Section: Introductionmentioning
confidence: 99%
“…5 Previous studies in different countries have shown that high level of mother’s NL has a significant and positive correlation with healthy nutrition and good nutritional outcomes in their offspring. 6 - 10 …”
Section: Introductionmentioning
confidence: 99%